2018
DOI: 10.1159/000494011
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Supplementation Attenuates Cardiac Remodeling After Experimental Myocardial Infarction

Abstract: Background/Aims: The objective of our study was to evaluate the effects of zinc supplementation on cardiac remodeling following acute myocardial infarction in rats. Methods: Animals were subdivided into 4 groups and observed for 3 months: 1) Sham Control; 2) Sham Zinc: Sham animals receiving zinc supplementation; 3) Infarction Control; 4) Infarction Zinc. After the followup period, we studied hypertrophy and ventricular geometry, functional alterations in vivo and in vitro, changes related to collagen, oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…The short-term inhalation of ultrafine zinc particles slowed down cardiac impairments caused by the myocardial infarction. The role of zinc as a modulator of cardiac changes has been recognized, which could affect homeostasis, oxidative stress, immune function, apoptosis, and ageing (Chasapis et al, 2012;Andrea et al, 2018). Zinc, a vital antioxidative element, can protect myocyte membrane against unsaturated lipids and inflammatory cytokines (Hennig et al, 1996) and thus alleviate the infarction-induced heart failure (Shokrzadeh et al, 2009) albeit there was much debate about the role of zinc concentrations in different types of cardiomyopathy (Marin and Rodriguez-Martinez, 1995;Kosar et al, 2006).…”
Section: Dysfunctions and Remodelingmentioning
confidence: 99%
“…The short-term inhalation of ultrafine zinc particles slowed down cardiac impairments caused by the myocardial infarction. The role of zinc as a modulator of cardiac changes has been recognized, which could affect homeostasis, oxidative stress, immune function, apoptosis, and ageing (Chasapis et al, 2012;Andrea et al, 2018). Zinc, a vital antioxidative element, can protect myocyte membrane against unsaturated lipids and inflammatory cytokines (Hennig et al, 1996) and thus alleviate the infarction-induced heart failure (Shokrzadeh et al, 2009) albeit there was much debate about the role of zinc concentrations in different types of cardiomyopathy (Marin and Rodriguez-Martinez, 1995;Kosar et al, 2006).…”
Section: Dysfunctions and Remodelingmentioning
confidence: 99%
“…Moreover, a reduced serum zinc level could be harmful to antioxidant defenses, leading to oxidative stress-induced cardiomyocyte necrosis [ 38 ]. In an animal study, zinc was shown to attenuate cardiac remodeling through the modulation of antioxidant enzymes [ 17 ]. In addition, a randomized control trial evaluating nutritional supplementation, including zinc, in patients with heart failure found an improvement in LV end-diastolic volume after treatment [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 40–78% of patients undergoing HD have been reported to have a zinc deficiency [ 14 , 15 ]. The effects of pharmacological strategies targeting diastolic dysfunction in HD patients remain unsatisfactory [ 16 ]; however, accumulating evidence indicates that zinc plays a pivotal role in attenuating cardiac remodeling through the modulation of antioxidant enzymes [ 17 , 18 ]. Furthermore, a recent meta-analysis of 27 case–control studies reported significantly lower serum zinc levels in patients with heart failure than in control subjects [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…O tamanho da amostra utilizada baseou-se em outros estudos realizados em nosso laboratório. 3,8,25 O número de ratos no grupo infartado foi maior, uma vez que a mortalidade esperada para esses animais durante o período experimental é de aproximadamente 50%. Além disso, somente animais com área infartada do VE maior que 30% foram incluídos no estudo.…”
Section: Protocolo Experimentalunclassified